Prevalence of glaucoma in Eastern India: The Hooghly River Glaucoma Study - Chandrima Paul; Subhrangshu Sengupta; Sumit Choudhury; Souvik Banerjee; Betsy L Sleath (Indian Journal of Ophthalmology, 2016)
Context: Glaucoma is the leading cause of global irreversible blindness. No recent study with adequate sample size has been carried out to estimate glaucoma prevalence in Eastern India. Aims: The aim of this study was to assess and compare the prevalence and types of glaucoma in a rural and urban East Indian population. Settings and Design: The Hooghly River Glaucoma Study (HRGS) is a population-based cross-sectional study from West Bengal. A tertiary hospital in Kolkata was our urban study center. Our rural study area included 28 contiguous villages from the district of Hooghly surrounding the rural base hospital located at Dhobapara in village Bakulia. Individuals aged 40 years and above were included in this study. Subjects and Methods: All subjects underwent a detailed ophthalmic examination at our base hospitals including applanation tonometry, ultrasound pachymetry, gonioscopy, and frequency doubling technology perimetry. Glaucoma was defined using modified International Society of Geographical and Epidemiological Ophthalmology criteria. Statistical Analysis Used: Analysis was performed using Chi-square test and multiple logistic regression using SPSS. Results: Totally, 14,092 individuals participated; 2.7% were detected to have glaucoma in rural arm and 3.23% in urban arm (P < 0.001). In urban population, 2.10% had primary open angle glaucoma (POAG), 0.97% had primary angle closure glaucoma (PACG), and 0.15% had secondary glaucoma. In rural population, 1.45% had POAG, 1.15% had ACG, and 0.10% had secondary glaucoma. Conclusions: HRGS is the largest population-based glaucoma study in India to date with glaucoma prevalence comparable to other landmark Indian studies. POAG was the most common form of glaucoma in our study population as well. PACG was more common in this region than previously thought.